2004
DOI: 10.1093/annonc/mdh404
|View full text |Cite
|
Sign up to set email alerts
|

Weekly paclitaxel combined with pegylated liposomal doxorubicin (Caelyx™) given every 4 weeks: dose-finding and pharmacokinetic study in patients with advanced solid tumors

Abstract: The combination of PLD/wPTX constitutes an active chemotherapy regimen with mild toxicity that merits investigation in phase II at 30/80 or 35/70 mg/m(2). Patients should be monitored for a potentially increased risk of thromboembolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…These complex time-and dosedependent tumor priming effects of paclitaxel and the multidimensional drug-drug interactions highlight the need of careful considerations in using paclitaxel in combination therapy. For the combination of paclitaxel and doxorubicin HCl liposomes, the several schedules under clinical evaluation involve using concurrent administration (Campos et al, 2003;Briasoulis et al, 2004). Our current finding that a paclitaxel pretreatment improved the tumor-selective delivery and efficacy of doxorubicin HCl liposomes would support a schedule of administering paclitaxel before doxorubicin HCl liposomes to take advantage of the tumor priming property of paclitaxel.…”
Section: Latexmentioning
confidence: 76%
See 1 more Smart Citation
“…These complex time-and dosedependent tumor priming effects of paclitaxel and the multidimensional drug-drug interactions highlight the need of careful considerations in using paclitaxel in combination therapy. For the combination of paclitaxel and doxorubicin HCl liposomes, the several schedules under clinical evaluation involve using concurrent administration (Campos et al, 2003;Briasoulis et al, 2004). Our current finding that a paclitaxel pretreatment improved the tumor-selective delivery and efficacy of doxorubicin HCl liposomes would support a schedule of administering paclitaxel before doxorubicin HCl liposomes to take advantage of the tumor priming property of paclitaxel.…”
Section: Latexmentioning
confidence: 76%
“…A potential mechanism of the greater tumor delivery of doxorubicin HCl liposomes in the tumor priming group is a reduced doxorubicin clearance by paclitaxel (Briasoulis et al, 2004). This was ruled out because pharmacokinetic results, together with statistical analysis using the bootstrap (see Materials and Methods), indicated that tumor priming did not alter the area under the plasma concentration-time curves of total doxorubicin (sum of free and liposome-entrapped drug).…”
Section: Resultsmentioning
confidence: 99%
“…For example, pegylated liposomal doxorubicin has been shown to produce higher plasma levels when coadministered with paclitaxel. 51 However, one should remember that, in the setting of lack of direct confirmatory drug interaction studies of nab-paclitaxel, these interactions are only based on assumption from extrapolation of paclitaxel interactions. Moreover, the drug-drug interaction may not always be clinically relevant (eg, minimal pharmacokinetic changes from clindamycin-paclitaxel combination and minimally increased plasma paclitaxel when given in combination with pazopanib).…”
Section: Gupta Et Almentioning
confidence: 99%
“…In phase I work, PLD was combined with ifosphamide, 58 topotecan (oral 59 or intravenous [60][61][62] ), etoposide, 63 taxanes, [64][65][66][67] platinums, [68][69][70][71] vinorelbine, 24,72 gemcitabine, 73,74 and capecitabine. 75 These trials are reviewed in Table 3, which summarizes the relevant maximum tolerated dose toxicities.…”
Section: Ongoing Development Of Pldmentioning
confidence: 99%